Hubungan antara Investment Opportunity Set dan Kebijakan Dividen Pada Perusahan yang Listing di Bursa Efek Indonesia - Azmi Fasa (Ma'soem University, 2023)
Company growth is a problem faced by every company. The growth of the company can be seen from the firm value. Companies are very careful to determine a policy, because a policy can have an impact on firm value. The purpose of the company itself is to maximize the firm value , because this is can increase owner whealth. Therefore many companies are competing to increase the firm valu. One that affects the value of the industry is the dividend policy. This research aims to determine the relationship between dividend policy and company growth proxied by the investment opportunity set (IOS) in companies listed on the Indonesian Stock Exchange (IDX). In this research, researchers used a correlational study which is part of a causal research design using a stratified random sampling technique. IOS is proxied by the following ratios including: Capital Additional per Market Value of Assets (CAPMVA), Price Earning Ratio (PER), Market Value of Equity to Book Value of Equity (MVEBVE), Market Value of Assets to Book Value of Assets ( MVABVA), and Additional Capital per Book Value of Assets (CAPBVA). This research result a conclusion regarding the phenomenon that occurs on the Indonesia Stock Exchange (IDX), that are companies listed on the IDX are dominated by growing companies, then the majority of companies listed on the IDX tend to allocate company profits for future investment rather than being distributed to investors through dividends. Another conclusion obtained from this research is that there is a significant positive relationship between dividend policy and investment opportunity sets with a correlation value of 0.279.